2021
DOI: 10.3389/fpls.2021.672702
|View full text |Cite
|
Sign up to set email alerts
|

Enzymology and Regulation of δ1-Pyrroline-5-Carboxylate Synthetase 2 From Rice

Abstract: Under several stress conditions, such as excess salt and drought, many plants accumulate proline inside the cell, which is believed to help counteracting the adverse effects of low water potential. This increase mainly relies upon transcriptional induction of δ1-pyrroline-5-carboxylate synthetase (P5CS), the enzyme that catalyzes the first two steps in proline biosynthesis from glutamate. P5CS mediates both the phosphorylation of glutamate and the reduction of γ-glutamylphosphate to glutamate-5-semialdehyde, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 72 publications
2
28
1
Order By: Relevance
“…Through diverse molecular methods, key genes involved in proline biosynthesis and degradation (proline cycle; Figure 1 ) have been identified in plants ( Deuschle et al, 2001 ). The enzymes P5CS1 and P5CS2 (EC 2.7.2.11, two isoforms) utilize either NADH or NADPH ( Chen et al, 2006 ; Forlani et al, 2017 ) and ATP to produce P5C and their activities are subjected to feedback inhibition by proline, other amino acids and cofactors ( Sabbioni et al, 2021 ). Millimolar levels of proline have been found inhibitory to rice P5CS2 enzyme.…”
Section: Proline Cycle Modulation By Redox Status and The Expression ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Through diverse molecular methods, key genes involved in proline biosynthesis and degradation (proline cycle; Figure 1 ) have been identified in plants ( Deuschle et al, 2001 ). The enzymes P5CS1 and P5CS2 (EC 2.7.2.11, two isoforms) utilize either NADH or NADPH ( Chen et al, 2006 ; Forlani et al, 2017 ) and ATP to produce P5C and their activities are subjected to feedback inhibition by proline, other amino acids and cofactors ( Sabbioni et al, 2021 ). Millimolar levels of proline have been found inhibitory to rice P5CS2 enzyme.…”
Section: Proline Cycle Modulation By Redox Status and The Expression ...mentioning
confidence: 99%
“…Millimolar levels of proline have been found inhibitory to rice P5CS2 enzyme. Similarly, analogs of proline like azetidine-2-carboxylate, pipecolate, hydroxyproline, phosphonoproline displayed the ability to bind to the enzyme rice P5CS2 and inhibit the activity aside cofactors such as NAD + and ADP ( Sabbioni et al, 2021 ). These results infer that structural analogs of proline inhibit the P5CS2 enzyme like that of proline feed-back inhibition.…”
Section: Proline Cycle Modulation By Redox Status and The Expression ...mentioning
confidence: 99%
“…The full-length wild-type or mutant P5CS (100 nM protein) activity was determined in the reaction buffer containing 25 mM HEPES pH 7.5, and 10 mM l -glutamate (Sigma), with added 20 mM MgCl 2 , 10 mM ATP (Takara), and 0.5 mM NADPH (Roche) used to initiate the reaction ( Magini et al, 2019 ; Sabbioni et al, 2021 ), then the reaction was monitored at 37°C in an MD-SpectraMax i3 plate reader and absorbance at 340 nm was measured every 20 s for 10 min (one experiment, n = 3). The NADPH concentration was converted from A340 with the standard curve determined at the same experiment.…”
Section: Methodsmentioning
confidence: 99%
“…A maximum likelihood tree reconstruction suggests that this legume-specific form derives from a duplication of P5CS2 ( Figure 2 ). It would be interesting to assess whether Mt P5CS3 is also subjected to peculiar post-translational regulation mechanisms, such as a lack of feed-back inhibition by proline, yet this aspect has been poorly investigated to date ( Sabbioni et al, 2021 ). Anyway, its emergence seems to imply that a higher demand for proline is connected with symbiotic nitrogen fixation, and further strengthens the possibility that high proline levels are needed for an optimal functioning of the nodule under stress.…”
Section: High Proline Levels In Legumes As Determined By a Specific F...mentioning
confidence: 99%
“…Although the possibility that proline may act as ROS scavenger has not been confirmed ( Forlani et al, 2019 ), several recent studies showed that the interconversion of glutamate and proline may regulate the redox balance and the energy status of the cell in connection with other redox shuttles ( Zheng et al, 2021 ). Accordingly, most enzymes in proline metabolism influence, and are regulated by, the intracellular NAD(P) + /NAD(P)H ratio ( Giberti et al, 2014 ; Sabbioni et al, 2021 ). Therefore, active proline metabolism in nodules could be involved in generating ROS and/or maintaining redox levels required for a proper establishment of the symbiosis.…”
Section: Possible Roles For Proline In the Establishment Of The Legum...mentioning
confidence: 99%